Fecal Fermentation Profile, Serum Fatty Acid Profile and Measures of Liver Health in Male HIV-infected Versus Non-infected Controls. (29th May 2020) - Andreae, Mary; Clark, W Andrew; Sterrett, John; Adkins, James; Smith, Konner; McGinnis, Joel; Peterson, Jonathan; Moorman, Jonathan
Abstract: Objectives: Many persons with an HIV infection and undergoing treatment still experience weight loss, hyperglycemia, hyperlipidemia, gastrointestinal issues (diarrhea and malabsorption), and symptoms of lipodystrophy. Symptoms include NAFLD and liver fibrosis. The gut microbiota and short chain volatile fatty acids (SCVFA) interface with other body systems. Dysbiosis of the gut microbiota due to pharmaceuticals, malabsorption, and chronic diseases is associated with milieu of imbalances indicated by the modification of the SCVFA profile. This study aimed to further elucidate the relationship between gut microbiota fermentation profiles, serum and fecal long chain fatty acid profiles, NAFLD, liver fibrosis, and anthropometric measures in HIV infected males. Methods: This research enrolled 14 HIV-infected and 14 non-infected males that were matched for age and body mass index (BMI). Anthropometric measurements BMI and hip to waist ratio were obtained, along with a liver scan for fatty liver and fibrosis using the ARFI ultrasound technique as well as a single blood draw via venipuncture. A full bowel movement was collected for each participant, a small aliquot was collected for future microbiome analysis, and the remainder was freeze-dried and stored at −80 C. Proximate analysis of fecal fat content was analyzed by soxhlet extraction. Fermentation profile of both fecal SCVFA and LCFA, and serum LCFA were analyzed via gas chromatography. Results: Significant differences in levels of specific SCVFAs were found between groups, with male controls having significantly higher amounts of acetate ( P  < 0.046), butyrate ( P  < 0.033), and valerate ( P  < .006). Serum LCFA were similar between groups with a few exceptions. Anthropometric data approached statistical significance, with the HIV infected males exhibiting a greater value for liver damage ( P  = 0.060) and hip to waist ratio ( P  = 0.015). Conclusions: In addition to identifying altered lipid circulation and liver damage, this research suggests differences in microbial communities between HIV-infected and non-infected individuals. Planned future microbiome analysis will help to correlate bacterial populations with altered fecal fermentation profiles. Funding Sources: Seed Grant, Center of Excellence in Inflammation, Infectious Diseases and Immunity, ETSU.